PROFIL SOSIODEMOGRAFI DAN TERAPI ANTIRETROVIRAL PADA PASIEN HIV/AIDS RAWAT JALAN RSUD RADEN MATTAHER JAMBI PERIODE TAHUN 2017-2018 - Jelly Permatasari; Muhammad Budi; Indri Meirista (As-Syifaa Jurnal Farmasi, 2020)
As a result of the decline in the immune system it is very susceptible to various diseases (opportunistic Infections) that can be prevented by the presence of antiretroviral therapy with various complications. Sociodemographic Profile is a human picture related to the purpose of the study, Sociodemographic research in HIV / AIDS patients is still rarely found, therefore Sociodemographic Profile is important to know as a basis for information that can be used to prevent transmission of HIV / AIDS. The purpose of this study was to determine the Sociodemographic Profile and ARV therapy in outpatient HIV / AIDS patients at Raden Mattaher Jambi Hospital in the 2017-2018 period. This research method is descriptive by retrospectively collecting data from medical record data. The results showed in the Age group 26-35 years (41.94%), Male sex (70.97%), the last high school education (61.29%), Employee / Private employment history (54.84%) , based on the highest transmission Heterosexual (84.95%), with Marital marital status (83.87%), based on the highest HIV / AIDS status namely HIV (94.62%). Based on ARV therapy, most combinations of Efavirens + Lamivudin + Tenofovir (59.14%).